(untitled) (Journal of Surgical Sciences, 2020)
Background: Liver remains the second most common injured organ in both blunt and penetrating trauma of the abdomen. Management of blunt or penetrating injury to the liver remains a significant challenge to trauma surgeons. Unstable patients require immediate laparotomy. Selective patients can be managed without surgery and with careful monitoring. Mortality is mainly due to damage to major hepatic blood vessels, massive parenchymal and biliary injury. Associated non-hepatic injuries contribute greatly to the overall mortality. With improved understanding of the major causes of mortality from hepatic injury, adequate resuscitation, well planned surgical intervention and better intensive care facilities have decreased mortality and morbidity Objectives: Performed to assess incidence, mechanisms, management and outcome of traumatic liver injury. Methods: This prospective study was performed in Dhaka Medical College Hospital between January 2013 to December 2014. Sixty patients with hepatic injury were included in the study. Data collected in data collection sheet regarding demographic data, severity of liver injury, hemodynamic status on admission, investigations reports, concomitant injuries, management scheme, and outcome of patients which were then analyzed. Results: There were 39 male and 21 female patients with a mean age of 31.3 (SD=15.4) years. Road traffic accident was the most common injury mechanism (71%). 20 patients (33%) were in shock at the time of admission. 48 patients (80%) with liver injury had associated injuries of other organs. Majority of the patients (41%) were found with grade Ill injury. 50 patients (83%) needed surgical interventions. Most common (16%) complication was wound infection. 3 patients (5%) died in this series. 5 patients (8%) developed liver abscess on subsequent follow up. Conclusion: Most of the trauma victims are young and in the active state of life. Prompt resuscitative measures, assessment of extend of hepatic injury and associated injuries, well justified surgical intervention along with critical care support can contribute greatly to the survival of victims of hepatic injury. Journal of Surgical Sciences (2018) Vol. 22 (1): 36-42